Faktor-Faktor yang Mempengaruhi Tingkat Pengangguran di Kota Kendari - Dhea Hervina Subiyakta; Kiki Novitasari (Universitas Halu Oleo, 2020)
Unemployment is a problem that is not foreign experienced by developing countries,for example indonesia, which currently has a population of at most fourth in the world. The cause of the occurrence of unemployment caused by population growth is increasing year increased but the amount of field effort is still minimal and in addition also the rate of economic growth is increasing. In the city of Kendari, the relationship between economic growth and the unemployment rate in the year 2017-2019 contrast as that between the unemployment rate has a relation which is negative. Furthermore, to determine the relationship between the education level and the unemployment rate in the City of Kendari in the year 2017-2019 which states that the level of education is not constant against the increase in employment.